DETERMINAN KEPATUHAN WAJIB PAJAK UMKM DENGAN VARIABEL PREFERENSI RESIKO DAN VARIABEL KONDISI KEUANGAN SEBAGAI VARIABEL MODERASI (STUDI PADA WAJIB PAJAK UMKM DI KOTA MALANG) - FATHUR RAHMAN UTOMO (Jurnal Ilmiah Mahasiswa FEB, 2018)
This  study  aims  to  examine the influence  of  subjective  norms,  the  attitude  of  not supporting  tax  evasion,  and  perception  of  the  quality  of  tax  service  on  the compliance of SMEs taxpayer, and the influence moderation of risk preference on the perception relation of the tax service quality with  taxpayer compliance, and the influence  of  the  moderation  of  the  financial  condition  tax  service  and  taxpayer compliance. The object of this research  is taxpayers who have SMEs in Malang. This study used the Theory of Planned Behavior (TPB) model, Theory of Prospect (TP), and Alabede et al. (2011). A total of 197 data were collected using survey data  with  non  probability  sampling  technique.  Metohed  of  data  analysis  using partial least square in application PLS. Test results show that subjective norm and attitude does not support tax evasion have a positive effect on taxpayer compliance, The effect of moderating risk preference has been shown to improve the relationship between attitude not supporting tax evasion with tax compliance. Meanwhile, the perception  of  the  quality  of    tax  service  has  a  negative  effect  on  taxpayer compliance,  so  that  the  condition  to  test  the  effect  of  moderation  of  financial condition was lost. The implication of this research is  the government should pay more attention to the financial condition of the taxpayer who has SMEs so as to minimize the occurrence of tax evasion, it has the possibility of influence over the subjective norm of the taxpayer so that it becomes obedient to the tax regulations.Keywords: taxpayer compliance, Theory of Planned Behavior, moderation of risk preference, moderation of financial condition